Pattern of skin cancer at Dammam Medical Complex in Dammam, Saudi Arabia - Khalid M. Alwunais; Sohail Ahmad (Wolters Kluwer Medknow Publications, 2016)
Objective: This study was performed to determine the pattern of skin malignancies in Dammam Medical Complex, Dammam, Kingdom of Saudi Arabia and to compare these results with those from other parts of the world. Materials and methods: Histologically diagnosed skin cancers between June 2008 and May 2014 were reviewed and analyzed. Dammam Medical Complex is the main hospital in Dammam that receives most of the malignant cases in this area. Trends in incidence of skin cancers by their age, sex and anatomic location were examined. Results: Of the 27 cases of skin cancer majority (74%) were Saudis and males (59.2%). The most common malignant skin lesion was BCC followed by SCC, dermatofibrosarcoma protuberans (DFSP), skin secondaries from stomach, breast and lung, mycosis fungoides (MF), malignant melanoma (MM). The most common site was head and neck for BCC, trunk for SCC, and trunk for DFSP. Conclusion: Low occurrence of malignant skin tumors is found in dermatology practice in Dammam. Nevertheless BCC, SCC and MM should be considered in the dermatology practice locally. The most common skin cancers seen are BCC and SCC followed by DFSB and MF. The site of distribution of BCC and SCC in our study is similar to studies from various other regions of Saudi Arabia and other countries.